Security and privacy issues of electronic healthcare system: A survey. Issue 8 (17th November 2019) - Singh, Ashish; Chatterjee, Kakali
Abstract: In today's digital environment, the paper-based healthcare system shifts towards the Electronic Healthcare System (EHS). The EHS features will allow its user to access the healthcare data and resources anywhere in the world-wide with the help of the Internet. This will improve the access and sharing, healthcare quality, treatment procedure, efficiency and reduce the care cost and time of the EHS. Regardless of the advantages, the transformation from a paper-based healthcare system to EHS has brought many security and privacy issues such as access control, trust, authentication, transmission of data, sharing, delegation, abuse use of healthcare data, data confidentiality and integrity, and many more. Due to such issues, there is a need to be the focus on the security and privacy issues in the EHS. Thus, in this paper, we focus on many security and privacy issues present in the modern EHS. The paper discussed the architecture of the modern EHS. Additionally, we have discussed the security analysis of the EHS. The given security analysis and solutions of EHS will help the EHS research people to design a more secure and robust healthcare system.